2011
DOI: 10.5693/djo.02.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative spontaneous bilateral suprachoroidal hemorrhage

Abstract: SummarySuprachoroidal hemorrhage is a rare condition, occurring most commonly in the perioperative period, although cases of unilateral spontaneous hemorrhages have been reported. We report a case of bilateral spontaneous suprachoroidal hemorrhage and discuss the potential causative factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Previously, bilateral SCH has been reported in only one clinical case [16], in which the cause of SCH was considered to be lower respiratory tract infection and coughing (Valsalva maneuver) combined with a raised prothrombin time-international normalized ratio [16]. The Valsalva maneuver inhibits venous return by increasing intrathoracic pressure; the resulting increase in venous pressure leads to SCH (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previously, bilateral SCH has been reported in only one clinical case [16], in which the cause of SCH was considered to be lower respiratory tract infection and coughing (Valsalva maneuver) combined with a raised prothrombin time-international normalized ratio [16]. The Valsalva maneuver inhibits venous return by increasing intrathoracic pressure; the resulting increase in venous pressure leads to SCH (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…We believe that the duration of increasing intrathoracic pressure as a result of being under the snow pile was very short. Clinically, SCH has been shown to occur with a short period of dyspnea [16]. We also think that the weight of the snow pile before she died was not heavy enough to cause traumatic asphyxia, because of the evidence that she was alive for several hours after SCH onset; the rest of the snow, which would have added enough weight to result in immediate death, had to have fallen after she died.…”
Section: Discussionmentioning
confidence: 97%
“…SSCH is an infrequent condition, characterised by an unfavourable visual prognosis 8 , 11 . Literature is scarce of reports presenting SSCH development in patients with no predisposing systemic or ocular conditions, and very few of them with bilateral involvement 14 , 15 , 16 , 17 .…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis showed that abnormal coagulopathy and the use of anti-coagulants were both major risk factors in spontaneous SCH in patients aged over 60, associated with 82.6% and 69.6% of the cases respectively [32]. With regards to use of warfarin, spontaneous SCH can occur when the INR is within or over therapeutic range [33,34].…”
Section: Discussionmentioning
confidence: 99%